KOMISI KODE ETIK POLRI SEBAGAI LEMBAGA AD HOC KEPOLISIAN DALAM PENEGAKAN KODE ETIK PROFESI POLRI - Marsudianto (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2015)
The purpose of this study is to know and describe the efforts made by the Commission of Police Ethics Code (KKEP) in the enforcement of the code of ethics of the Police profession as well as what factors led to the enforcement of the code of ethics of the Police profession. The research method in this research is empirical research by using qualitative approach, which is to search the object of research, describe, and understand its meaning. Data collection techniques used in this study are interviews, and documentation, which then analyzed qualitatively. The results of the research indicate that the factors of the professional code of ethics is that every Performance of any member or officer who neglects or intentionally commits a violation or a crime of a crime may result not only to the member of the offender, but may also have implications for the Polri institution directly or can not directly affect the decline or loss of confidence in the image of the Police. Efforts made by the KKEP in enforcing the Code of Ethics of the Police Profession is to remain guided by existing regulations, and to forward the personal Tri Bhayangkara Police who are subject to the prohibitions as the State's honorable institution.